2005
DOI: 10.1016/j.theriogenology.2005.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of yearling beef bulls during mating

Abstract: Crossbred (Bos taurus) yearling beef bulls were assessed for breeding soundness and physical traits prior to multi-sire natural mating at pasture. Bulls (n = 60) were assigned to six groups of nine or 10 bulls and two bull-groups were rotated on 14-day intervals during a 63-day mating season in each breeding herd (n = 3) of 191-196 cows. The remaining bulls (n = 14) were maintained under similar environmental conditions without mating exposure. Bulls were observed during mating and assessed for breeding soundn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 18 publications
(24 reference statements)
2
26
0
Order By: Relevance
“…The physical causes of failure are consistent with other findings (McGowan et al, 2002;Cumming, 2003), suggesting that bulls develop problems along their service in the field (Ellis et al, 2005), especially in large natural pasture areas with irregular topography, which requires more physical activity during the breeding season. The mounting activity over the years leads to a natural wear of the bull's physical ability, mainly affecting the locomotor system.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The physical causes of failure are consistent with other findings (McGowan et al, 2002;Cumming, 2003), suggesting that bulls develop problems along their service in the field (Ellis et al, 2005), especially in large natural pasture areas with irregular topography, which requires more physical activity during the breeding season. The mounting activity over the years leads to a natural wear of the bull's physical ability, mainly affecting the locomotor system.…”
Section: Discussionsupporting
confidence: 88%
“…It is well-documented that bull selection affects the performance of the herd (Parkinson, 2004;Ellis et al, 2005); therefore the use of reliable methods to evaluate the reproductive potential, such as the bull breeding soundness evaluation (BBSE), is critical in ranch management.…”
Section: Introductionmentioning
confidence: 99%
“…An overall breeding soundness examination (OBE) is a quick, reliable and cost-effective method of screening and classifying bulls in terms of breeding potential (Ellis et al 2005). The latter as well as fertility tests before the onset of the breeding season contribute significantly towards better conception rates in beef herds.…”
Section: Managing Reproduction Within a Resource Limiting Environmentmentioning
confidence: 99%
“…Yearling beef bulls are an important component of natural mating schemes and the principal method employed to assess the reproductive potential of the bulls, and thus selection of the bulls, is by overall breeding soundness examinations (OBE) (Ellis et al, 2005). An OBE is a quick, reliable and cost-effective method of screening and classifying bulls in terms of breeding potential and thereby minimizing the use of sub-fertile bulls.…”
Section: Introductionmentioning
confidence: 99%
“…Yearling beef bulls are typically selected as potential herd sires on their performance in a growth performance test. Data are lacking on the relationship between performance test results and reproductive parameters, but previous results suggested that an unfavourable relationship exists (Ologun et al, 1981;Ellis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%